Tantangan yang Dihadapi Guru IPA dalam Menerapkan Pembelajaran berdiferensiasi di SMP Palu Sulawesi Tengah Indonesia - Nurasyah Dewi Napitupulu; Bau Ratu; Daud K Walanda; Mery Napitupulu (Jurnal Penelitian Pendidikan IPA, 2023)
Within the ever-evolving scene of instruction, the usage of differentiated learning, an approach planned to cater to assorted student’s needs, has picked up unmistakable quality. This article investigates the challenges experienced by science teachers as they explore the complexities of joining differentiated learning procedures into their classrooms in junior high schools in Palu, Central Sulawesi-Indonesia. A mixed-methods investigative plan, comprising overviews and interviews, was utilized to explore the encounters of science teachers. The quantitative stage uncovered that whereas a critical parcel of teachers grasped differentiated learning, they experienced challenges such as time limitations (80%), substance adjustment (50%), constraints to fitting educating assets (20%), students’ resistance (30%), and inadequately proficient improvement (20%). The subjective stage gives in-depth experiences into these challenges, highlighting the requirement for imaginative procedures, progressing back, and asset accessibility to overcome them. The consideration underscores the significance of tending to these challenges to cultivate a more comprehensive and locks-in science teaching-learning environment that benefits both teachers and students